Impuesto sobre la renta personas naturales según la Ley 2277 del año 2022 (2023)
Colombia has been considered a country with low-income tax collection for natural persons; however, tax changes have been made very constantly with the aim of improving this problem, Law 2277 of 2022 has significant modifications in this area.